PENGARUH PENGEMBANGAN KARIR, KARAKTERISTIK INDIVIDU DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA FIFGROUP DENPASAR - I Made Bagus Ary Permana; I Nengah Sudja; Ida Bagus Made WIdiadnyana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
Performance is the result of employee work in a certain period. The research was conducted due to aphenomenon, namely fluctuations in non-performing loans which indicated a lack of opportunities to develop careers and employees were less interested in the work provided, employees also expressed objections when asked to workovertime. This study aims to determine the effect of career development, individual characteristics and organizational commitment on employee performance at FIFGROUP Denpasar. The research was conducted at FIFGROUP Denpasar where there have been fluctuations in bad loans for the last 3 years. The population is all employees as much as 65 respondents and the sample is determined by the method of determining the sample using a census technique. Data was collected through observation, documentation studies, interviews and questionnaires. The analysis technique used is multiple linear regression. The results show that career development has a positive and significant effect on the performance of FIFGROUP Denpasar employees, individual characteristics have a positive and significant impact on the performance ofFIFGROUP Denpasar employees and organizational commitment has a positive and significant impact on theperformance of FIFGROUP Denpasar employees.